Responsibility to protect in Southeast Asia and the role of civil society organizations as norm entrepreneurs - Tana, Maria Thaemar (Animo Repository, 2013)
The article looks into responsibility to protect (R2P) in Southeast Asia and the role of civil society organizations (CSOs) as norm entrepreneurs. Using Finnemore and Sikkink's "norm life cycle" theory, it is argued that civil society organizations contribute to the emergence of the R2P norm in the region; however, for the norm to be fully "internalized" by target states, it needs to be constitutively localized-that is, it needs to be reconciled with preexisting regional and domestic norms. CSOs need to engage governments, domestic political leaders, and local nongovernmental organizations in order for R2P to be applied in a manner consistent with the ASEAN Way and ASEAN states' interests, preferences, and priorities. © 2013 De La Salle University, Philippines.